3x 5x^3-x^2-5x 1

3x 5x^3-x^2-5x 1

Simplifying (5x + - 3)(x + - 2)(2x + 5) + - 1 (3x + - 2)(2x + -5)(x + -4) = 0 Reorder the terms: (- 3 + 5x)(x + - 2)(2x + 5) + - 1 (3x + - 2)(2x + -5)(x + -4) = 0 Reorder the terms.
Solve for x 2 / 5x - 1 / 3x =2. 25x− 13x =2 2 5 x - 1 3 x = 2. Simplify the left side. Tap for more steps Simplify each term. Tap for more steps Simplify 25x 2 5 ⁢ x.
Tiger helps you with your homework and shows you, step by step how to Solves Quadratic Equations { 3x ^ 2 - 5x + 1 =0} by Completing the Square, Quadratic.
6x+5(2-3x)=3(2x -1) Multiplication and Division, Addition and Subtraction. Observation : No two such factors can be found!! A future release will add this functionality. Hint: Selecting "AUTO" in the. Note: exponents must be positive integers, no negatives, decimals, or variables. Then it will attempt to solve the equation by using one or more of the following: addition, subtraction. 3x 5x^3-x^2-5x 1